Issues in rice marketing system: a case of central terai - Kharel, Meena; Timsina, Krishna Prasad; Adhikari, Surya Prasad; Ghimire, Yuga Nath; Gairhe, Samaya; Devkota, Deepa; Poudel, Hema Kumari (Journal of Agriculture and Natural Resources, 2022)
This study was conducted to understand the challenges and prospects of ricemarketing by taking case of central Nepal. Two focus group discussionsalong with eight key informants’ interviewswere conductedinBara and Parsa districts of Nepal.Also, secondary information was collected by reviewing the related literatures.The study revealed that the consumer price of rice is almost double than the farm gate price, possibly due to the presence of several intermediaries in different nodes of the supply chain.Key market actors like large collectors, millers and wholesalers have a dominating role in price negotiation and supply of rice in the market. The rice value chain is not strong enough, which might be due to poor vertical and horizontal as well as backward and forward linkages among the key players. The demand of fine and aromatic rice is gradually increasing due to changing food habits of the consumers and their access to purchasing capacity as well.The high yielding short duration varieties of fine and aromatic rice need to be identified and developed to meet the growing demand of consumers.In addition, to boost productivity and profitability of rice, a better investment climate, risk sharing mechanism and strengthened value chain with efficient research and extension services are required.